Pengaruh polisakarida dalam panax ginseng untuk vaksinasi flu burung (H5N1) - Herlambang, Geri Indra; Sangging, Putu Ristyaning Ayu (Wellness And Healthy Magazine, 2020)
Avian Influenza disease is caused by an avian influenza virus infection that became one of the biggest causes of death in the world. The subtype of the virus present in Indonesia is the H5N1 virus. According to the World Health Organization (WHO), in 2012, the outbreak of the H5N1 subtype avian influenza virus was first reported in 1996, Guangdong Province, South China, and spread to Indonesia since 2003. The number of death from avian influenza outbreak (H5N1) in Indonesia was recorded to be the highest in the world, with the number of death was 151 of 183 people who positively infected with the virus. The H5N1 virus can enter and infect humans when the body’s immune system of the person is low. Panax ginseng belongs to the Araliaceae family, which contains several components, such as ginsenosides, polyacetylenes, polyphenols, and polysaccharides. The Polysaccharides in Panax ginseng have an immunomodulatory function that can increase cytokine production and activate macrophages as an effort to improve and increase the body’s immune system. Therefore, polysaccharides in Panax ginseng affect avian influenza vaccination because it enhances the body’s immune response.